2016
DOI: 10.1186/s13014-016-0695-6
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal sparing radiotherapy for glioblastoma patients: a planning study using volumetric modulated arc therapy

Abstract: BackgroundThe purpose of this study is to investigate the potential to reduce exposure of the contralateral hippocampus in radiotherapy for glioblastoma using volumetric modulated arc therapy (VMAT).MethodsDatasets of 27 patients who had received 3D conformal radiotherapy (3D-CRT) for glioblastoma with a prescribed dose of 60Gy in fractions of 2Gy were included in this planning study. VMAT plans were optimized with the aim to reduce the dose to the contralateral hippocampus as much as possible without compromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
2
8
1
Order By: Relevance
“…The study by Posti et al 14 reported main presenting symptoms as seizures and cognitive disorder. Cognitive 17 study showed increased female cases, studies have shown that gender plays a prognostic role in survival of GBM cases due to estrogen hormone acting as a protective function though no clear-cut evidence could be collected, reseach work is ongoing to find out its importance but as far as our study is concerned, we found similar result as Canyilmaz et al 15 and Hofmaier et al 16 study.…”
Section: Agesupporting
confidence: 82%
“…The study by Posti et al 14 reported main presenting symptoms as seizures and cognitive disorder. Cognitive 17 study showed increased female cases, studies have shown that gender plays a prognostic role in survival of GBM cases due to estrogen hormone acting as a protective function though no clear-cut evidence could be collected, reseach work is ongoing to find out its importance but as far as our study is concerned, we found similar result as Canyilmaz et al 15 and Hofmaier et al 16 study.…”
Section: Agesupporting
confidence: 82%
“…The hippocampus has been shown to be important for several neurocognitive functions [ 23 26 ]. Thus, additionally to the common known structures like hippocampus, subventricular zone, amygdale and thalamus, it may be essential to focus also on the cerebral cortex as an important OAR [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant correlations between the doses delivered to the hippocampi and late decline in neuropsychological tests performed following focal brain radiotherapy have been highlighted [5]. Following these results, radiation techniques sparing the hippocampi, especially using intensity-modulated radiation therapy (IMRT) approaches have been developed [6].…”
Section: Introductionmentioning
confidence: 99%